2023
DOI: 10.1039/d3qi01525d
|View full text |Cite
|
Sign up to set email alerts
|

Site occupation and upconversion process enabled multicolor emission in a Gd3GaO6:Bi3+,Er3+ phosphor for quad-mode anti-counterfeiting

Zhijun Li,
Zeyu Lyu,
Pengcheng Luo
et al.

Abstract: Enabled by the site occupation dependent emission of Bi3+ and the upconversion process dependent emission of Er3+, quad-mode anti-counterfeiting with four distinguishable images is achieved with only the Gd3GaO6:Bi3+,Er3+ phosphor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Additionally, two peaks at ∼159.6 and 162.8 eV revealed the presence of Bi in lower valent oxidation states, i.e., Bi n+ (0 < n < 3). 37 The appearance of deconvoluted peaks of Bi 4f 7/2 and Bi 4f 5/2 levels at lower binding energies may be ascribed to the presence of metallic Bi (Bi 0 ) and Bi 2+ ions. 51−53 The Er 4d peaks were observed at ∼169.3 eV in XPS spectra in the 2 mol % Bi 3+codoped sample (Figure 1f).…”
Section: Hydrodynamic Size Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, two peaks at ∼159.6 and 162.8 eV revealed the presence of Bi in lower valent oxidation states, i.e., Bi n+ (0 < n < 3). 37 The appearance of deconvoluted peaks of Bi 4f 7/2 and Bi 4f 5/2 levels at lower binding energies may be ascribed to the presence of metallic Bi (Bi 0 ) and Bi 2+ ions. 51−53 The Er 4d peaks were observed at ∼169.3 eV in XPS spectra in the 2 mol % Bi 3+codoped sample (Figure 1f).…”
Section: Hydrodynamic Size Measurementmentioning
confidence: 99%
“…Next, the color tuning of UC emissions can be attained by modifying the local crystal field and dynamics of UC processes via defect engineering by doping impurity ions. ,, In recent years, various codopant ions, such as Mn 2+ , Cr 3+ , Li + , Na + , Mg 2+ , and Bi 3+ , have been explored for tuning the UC emissions. ,, It has been found that Bi 3+ codoping in Er 3+ -doped UC materials can modulate the UC emissions through crystal field distortion, energy transfer, defect tuning, and manipulation of nonradiative channels. Hence, investigating the effect of defect manipulation on the excited state absorption of NIR photons by Er 3+ ions will provide a better understanding of the role of defects on UC dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Gao et al proposed Zn 3 Ga 2 GeO 8 : Cr 3+ , Yb 3+ , Er 3+ , and Zn 1.6 Li 0.4 GeO 4 : Mn 2+ persistent phosphors as the luminescent inks. [10] However, the multi-modal emission of the above materials often requires co-doping or solid solution strategies to introduce more luminescent ions, which increases the cost and complexity of the material design and also increases the workload. [11] In addition, when a variety of rare earth ions are doped, there are also certain requirements for the crystal structure of the host.…”
Section: Introductionmentioning
confidence: 99%